Design-build : integrating craft, service, and research through applied academic and practice models - Winterbottom, Daniel M. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Design-Build provides everything you need to know about how to embark on a design-build project within a studio or professional practice setting. Design-build models have increased across academic programs worldwide, allowing students to address the real-world challenges of working in the community using a participatory design process. In practice, they offer a full partnership between the designer and builder to elevate design concepts and reduce project costs. Written by an experienced practitioner and educator, this book offers contextual background on the development of the design-build model in pedagogy and practice, guidance from inception to conclusion for classroom and field usage, discussions on the shift to community-engaged design, and inspirational examples from international case studies. Illustrated in full colour throughout, it looks at structuring a design-build firm, best-practice, efficiency, and the limitations of design-build as a practice model. This is the fundamental guidebook for those interested in developing or working for a design-build professional practice, academics leading design-build programs and students interested in social and environmental justice, education and practice through a design-build model"--
OCLC-licensed vendor bibliographic record.
Keywords: Architectural practice; Design-build process (Construction industry); ARCHITECTURE / Landscape